Language Variation Types and Its Functions Used by Transvestites on â€œThe Mommy Officialâ€ Youtube Channel - N, Nurtamin; H, Hasnani (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Sociolinguistics studies between language and society. Language variation performed by the transvestites in the YouTube Channel namely The Mommy Official is extremely unique andÂ  interesting to be researched because the transvestites in the video channel frequently uses special words that only can be understood by their members. Therefore, the research was made to find out the language variation and their functions used by transvestites in The Mommy Official YouTube channel. This is a qualitative descriptive study with all transvestites players in the channel as the objects of research. The key instrument of this research is the researchers. To help the process of analysis, the researchers also use supporting instrument namely mobile phone as the medium to observe the videos by watching it on YouTube. The researchers analyze the data in the form of words, phrases, sentences, and dialogues performed by the players of â€œThe Mommy Officialâ€ on YouTube. The results showed that language variation exists in the channel video and the functions of the language variation are: 1) to make a nuance of humor; 2) to make a mock; 3) to make an intimate relation; 4) to hide particular information; 5) to soften the words; and 6) to express feeling and mood.